OpenDropOff: An open‐source, low‐cost drop‐off unit for animal‐borne devices. Issue 9 (26th June 2019) - Rafiq, Kasim; Appleby, Rob G.; Edgar, Jason P.; Jordan, Neil R.; Dexter, Cathryn E.; Jones, Darryl N.; Blacker, Amy R. F.; Cochrane, Matthew
Abstract: The use of animal‐borne devices in wildlife studies is increasing due to the miniaturization of sensors and reductions in component costs. Retrieval of animal‐borne devices is often advantageous for several reasons, including data retrieval and animal welfare considerations; however, commercially available drop‐off units are often prohibitively expensive and/or unreliable. Here, we present 'OpenDropOff', an open‐source, low‐cost electronic drop‐off unit for remotely detaching animal‐borne sensors from individuals. OpenDropOff devices function by using heat, produced by running an electrical current through resistance wire (nichrome), to melt nylon (e.g. fishing) line, detaching sensors from animals at or after a pre‐determined time. OpenDropOff can be constructed using commercially available components (costing < USD $15 in total; approximately 10% or less of many commercially available drop‐off units) and can be customized to fit project‐ and species‐specific needs. Fourteen OpenDropOff devices have been field deployed on koalas ( Phascolarctos cinereus ) ( n  = 11), swamp wallaby ( Wallabia bicolor ) ( n  = 1), Australian brush turkey ( Alectura lathami ) ( n  = 1) and Australian white ibis ( Threskiornis molucca ) ( n  = 1), with the only detachment failure occurring after a device was damaged during the koala's unrelated death. OpenDropOff devices provide a wider range of researchers with a reliable, cost‐effective tool for detaching animal‐borne sensors. Their use could allow researchers to more efficiently allocate project resources, and their flexibility provides an opportunity to mitigate animal welfare concerns surrounding the use of animal‐borne devices.